Analysis of Time Dependent Effects in Radiation Epidemiology - Eckerberg ,Daniel (My University, 2024)
Starting with radium watch dial painters in the 1920s, numerous diverse populations have been monitored following significantly-above-background radiation exposures. It is well founded that doses exceeding 100 mGy have potential to induce negative health outcomes in humans. Health effects resulting from radiation doses below this level are not as well understood. Consequently, risks for outcomes in the 0-100 mGy low-dose range are often approximated by linear extrapolation to zero dose. This practice is known as the “linear no-threshold” model. Existing research related to the linear no-threshold model is discussed thoroughly in NCRP Commentary 27 (NCRP 2018).